The Physiological Functionality of PGR5/PGRL1-Dependent Cyclic Electron Transport in Sustaining Photosynthesis - Ma, Mingzhu; Liu, Yifei; Bai, Chunming; Yang, Yunhong; Sun, Zhiyu; Liu, Xinyue; Zhang, Siwei; Han, Xiaori; Yong, Jean Wan Hong (Frontiers in Plant Science, 2021)
The cyclic electron transport (CET), after the linear electron transport (LET), is another important electron transport pathway during the light reactions of photosynthesis. The PGR5(Proton Gradient Regulation 5)/PGRL1(PRG5-like photosynthetic phenotype 1) and the NADH dehydrogenase-like complex(NDH) pathways are linked to the CET. Recently, the regulation of cyclic electron transport around PSI has been recognized as crucial for photosynthesis and plant growth. Here, we summarized the main biochemical processes of the PGR5/PGRL1-dependent CET pathway and its physiological significance in protecting the photosystem II (PSII) and photosystem I (PSI), ATP/NADPH ratio maintenance, and regulating the transitions between LET and CET in order to optimize photosynthesis when encountering unfavourable conditions. A better understanding of the PGR5/PGRL1-mediated CET during photosynthesis might provide novel strategies for improving crop yield in a world facing more extreme weather events with multiple stresses affecting the plants.